Optimal privatisation design and financial markets - Stefano Bosi; Guillaume Girmans; Michel Guillard (Fondazione Eni Enrico Mattei (FEEM), 2001)
In this paper we consider various privatisation mechanisms in a general equilibrium model. We show that privatisation has no real effects, if the public sector is efficient and lump-sum taxes are implemented. The free distribution of public assets is financially neutral, whereas the sale of public assets is not. If taxes are not available, there is a privatisation mix allowing the economy to reach the first best. The maintain of some public property rights is justified, even if the public efficiency is removed.
Keywords: E44; G1; H4; L33; 330; Financial market development; privatisation; public good provision; public sector inefficiency; risk diversification; Privatisierung; Öffentliche Güter; Optimale Besteuerung; Finanzmarkt; Theorie